2018
DOI: 10.5582/bst.2018.01156
|View full text |Cite
|
Sign up to set email alerts
|

A novel compound heterozygous mutation in the <i>GJB2</i> gene is associated with non-syndromic hearing loss in a Chinese family

Abstract: Autosomal recessive (AR) non-syndromic hearing loss (NSHL) is the most common form of hereditary deafness. Mutations in the gap junction protein beta 2 (GJB2) gene encoding connexin 26 (Cx26) account for about 50% of cases of ARNSHL. In the current study, a combination of exome sequencing and Sanger sequencing in a Chinese Dong family with ARNSHL allowed identification of a novel compound heterozygous mutation c.240G>C(p. Q80H)/C.109G>A(p.V37I) in exon 2 of the GJB2 gene, which co-segregated with the disease p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…To date, four missense mutations (Q80K, Q80P, Q80R, and Q80H) and one nonsense mutation were reported at this position, which lead to HL and can be considered in the screening, identification, and study of people with deafness. 43 Therefore, this novel mutation in the GJB2 gene appears to cause HL in the Iranian population, especially in the Azeri population. Therefore, the mutation screening of GJB2 for c.238C>A; p. Gln80Lys is recommended in patients with HL, belonging to the Azeri ethnic group.…”
Section: Discussionmentioning
confidence: 96%
“…To date, four missense mutations (Q80K, Q80P, Q80R, and Q80H) and one nonsense mutation were reported at this position, which lead to HL and can be considered in the screening, identification, and study of people with deafness. 43 Therefore, this novel mutation in the GJB2 gene appears to cause HL in the Iranian population, especially in the Azeri population. Therefore, the mutation screening of GJB2 for c.238C>A; p. Gln80Lys is recommended in patients with HL, belonging to the Azeri ethnic group.…”
Section: Discussionmentioning
confidence: 96%
“…Different amino acids have different structures, and the chemical bonds around amino acids may also change after the mutation of amino acids, which affects the change of protein structure and then affects protein function. [23–26] The 3D model was constructed for structural analysis of WT/Mut TNC and TBC1D24 proteins to determine the pathogenicity of mutant TNC and TBC1D24 according to SWISS MODEL and AlphaFold online prediction program. Structural modeling demonstrated that the p.Thr951Ile and p.Arg524Trp variants altered the normal protein structure (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The ClinGen hearing loss expert panel determined that c.109G>A is a causative factor for autosomal recessive non-syndromic hearing loss with variable expression and incomplete penetrance 14 . According to ACMG, the c.109G>A variant is predicted to be a pathogenic variant 15 . In this study, five patients with the c.109G>A homozygous variant and two with heterozygous variants did not www.nature.com/scientificreports/ pass hearing screening.…”
Section: Discussionmentioning
confidence: 99%